Ten-year incidence of colorectal cancer following a negative screening sigmoidoscopy: an update from the Colorectal Cancer Prevention (CoCaP) programme. Issue 2 (15th December 2014) - Doria-Rose, V Paul; Levin, Theodore R; Palitz, Albert; Conell, Carol; Weiss, Noel S
Abstract : Objective: To examine the rates of colorectal cancer (CRC) following a negative screening sigmoidoscopy. Design: Cohort study. Setting: An integrated healthcare delivery organisation in California, USA. Participants: 72 483 men and women aged 50 years and above who had a negative screening sigmoidoscopy between 1994 and 1996. Those at elevated risk of CRC due to inflammatory bowel disease, prior polyps or CRC, or a strong family history of CRC were excluded. Main outcome measures: Incidence rates of distal and proximal CRC. Standardised Incidence Ratios were used to compare annual incidence rates of distal and proximal CRC in the cohort to expected rates based on Surveillance, Epidemiology, and End Results data. Additionally, rate ratios (RR) and rate differences (RD) comparing the incidence rate of distal CRC in years 6+ postscreening with that in years 1–5 were calculated. Results: Incidence rates of distal CRC were lower than those in the San Francisco Bay area population at large during each of the first 10 years postsigmoidoscopy screening. However, the incidence of distal CRC rose steadily, from 3 per 100 000 in the first year of follow-up to 40 per 100 000 in the 10th year. During the second half of follow-up, the rate of distal CRC was twice as high as in the first half (RR 2 .08, 95% CI 1.38 to 3.16; RD 14 per 100 000 person-years, 95% CI 6 to 22). Conclusions: Though still below population levels, the incidence of CRC during years 6–10 following a negative sigmoiodoscopy is appreciably higher than during the first 5 years.